SHARIAH COMPLIANT FIRMS AND RISK SHARING UNDER PANDEMIC ERA - Faruk Balli; Jardine A. Husman (Journal of Islamic Monetary Economics and Finance, 2022)
In this paper we analyse the Shari’ah Compliant (here after SC) firms and how do they share the output risk under pandemic era. Firms that are accepted to be SC, have been exposed to financial ratio restrictions (like debt ratios, profit ratio or current assets). For those firm not able to use debt to eliminate the income shocks, It is expected that firms after a negative output shock would be reflected to shareholders. In this paper, we measure to what extent SC firms share the risk of income shocks with the market and shareholders. Under pandemic era, SC firms have been exposed to substantial negative income shocks. For the sake of holding their SC certificates, debt leverage is not considered as an option but dropping (or cutting down) dividend payments would make the firms look bad, if they have not done it before. At this stage, firms that have the flexibility to share their income shocks with both market and shareholders before, i.e, produce more on boom market and distribute more dividends and produce less on recession and distribute less dividends, are performed better – stock prices returned to original levels earlier-during the pandemic area.